Resilience, various benefits, and constraints of rubber agroforestry systems in southern Thailand - Jongrungrot, V. (International Journal of Agricultural Technology, 2021)
The research finding found various margin resilience of the twelve rubber agroforestry plots, classified by resilience levels: 1) five plots with the high resilience; 2) six plots with the medium resilience; and 3) one plot with the low resilience. Timbers in rubber plots showed the high resilience and the plots had timbers left for income generation in the future. Duck and goat in rubber plots had flexible resilience. Also, they kept weeds in check by eating them and their feces acted as organic fertilizers. The sarjor-caju mushroom, vegetable fern, and straw mushroom under rubber plots generated the top three margins in 2019 and green products. Gnetums under the shade of rubber trees grew well and produced good-tasting leaves. Pineapple and sala under rubber trees grew well and were good quality fruits. However, mangosteen and longgong under rubber trees were characterized taller shapes with less harvesting than the typical monoculture. The recommendations for promoting rubber agroforestry suggested to practice in the future: 1) cut down stunted and diseased rubber trees and intercropped trees that cannot be harvested or in the case of new rubber plantings, expand rubber inter-row distances, to allow more sunlight into the plots and decrease competition of root system, 2) prune fruit intercrops to allow more sunlight entry and control the canopy, 3) choose a kind of intercrop suitable for the ecosystem in the plot and 4) choose kinds of intercrop appropriate to the farmer’s time availability, and need for income.